Partial Clinical Remission of Type 1 Diabetes: The Need for an Integrated Functional Definition Based on Insulin-Dose Adjusted A1c and Insulin Sensitivity Score - Nwosu, Benjamin Udoka (Frontiers in Endocrinology, 2022)
Despite advances in the characterization of partial clinical remission (PR) of type 1 diabetes, an accurate definition of PR remains problematic. Two recent studies in children with new-onset T1D demonstrated serious limitations of the present gold standard definition of PR, a stimulated C-peptide (SCP) concentration of >300 pmol/L. The first study employed the concept of insulin sensitivity score (ISS) to show that 55% of subjects with new-onset T1D and a detectable SCP level of >300 pmol/L had low insulin sensitivity (IS) and thus might not have been in remission when assessed by insulin-dose adjusted A1c (IDAA1c), an acceptable clinical marker of PR. The second study, a randomized controlled trial of vitamin D (ergocalciferol) administration in children and adolescents with new-onset T1D, demonstrated no significant difference in SCP between the ergocalciferol and placebo groups, but showed a significant blunting of the temporal trend in both A1c and IDAA1c in the ergocalciferol group. These two recent studies indicate the poor specificity and sensitivity of SCP to adequately characterize PR and thus call for a re-examination of current approaches to the definition of PR. They demonstrate the limited sensitivity of SCP, a static biochemical test, to detect the complex physiological changes that occur during PR such as changes in insulin sensitivity, insulin requirements, body weight, and physical activity. These shortcomings call for a broader definition of PR using a combination of functional markers such as IDAA1c and ISS to provide a valid assessment of PR that reaches beyond static changes in SCP alone.